Influencia del aloe-vera sobre la resistencia a la Compresión, infiltración, absorción capilar, tiempo de Fraguado y asentamiento en un concreto estructural - Aburto Moreno, Zenown Ali Elbinz (2018)
In this research the influence of the percentage of Aloe Vera on compressive strength, infiltration, capillary absorption, time of setting and settlement in a structural concrete is evaluated in order to determine the most optimum percentage by analyzing the fresh and hardened condition of the concrete. Costs was computed for the conformation of a cubic meter of concrete using industrialized additives (Sika) and Aloe vera. Fine aggregate was used with fineness modulus of 2.5, coarse aggregate of nominal maximum size of ¾ in. and type ICo cement. A study of the parts of the Aloe vera plant added in the concrete by the drip test was carried out, with which its best use was determined. A concrete mix design was performed according to ACI 211 (American Concrete Institute). The use of Aloe vera was in percentages of 1, 2, 3, 4, 5 and 6% with respect to the total of the concrete, using the liquefaction technique to obtain this natural addition. The tests were carried out under the American Society for Testing Materials (ASTM) standards C39, C1701, C403 and C143 and A Spanish Norm - European Norm (UNE-EN 1925). It was found that the water content of the Aloe vera gel was 98%, the best use of the plant was with the bark, gel 2mm and the Aloin contained between these two membranes. The settling decreased linearly by returning a minimum workable mixture up to 2% addition (1"), for this percentage the initial setting favored almost double the time and approximately 7.6 times more for the final setting. The compressive strength reached its maximum value with addition of 2% Aloe vera, reaching 355 kg/cm2 (increase of 41% of compressive strength). Permeability decreased by 47.9% in terms of infiltration rate with a value of 0.039 in/hr to 2% of Aloe vera. Capillary absorption decreased 32% reaching a value of 1.9 g/m2xseg0.5 also at 2% addition of Aloe vera. The majority of trials studied showed that the use of 5% and 6% addition of Aloe vera did not improve the properties of concrete by excessive content.